Takaful participation readiness model (TPRM): the influence of takaful knowledge, religious commitment and materialism with the moderating effect of switching costs - Hartini Ab Ghani
Takaful (Islamic Insurance) was introduced in Malaysia to provide a better alternative for Muslims. As Muslims are known to be very concerned with religious obligation, family Takaful, thus, should be the life insurance coverage of choice. However, despite the obligation of having family Takaful and Muslim is the predominant religion in Malaysia, the penetration rate of family Takaful in 2013 was only 14 percent as compared to conventional life insurance of 55 percent. It is therefore essential to investigate the factors causing or inhibiting the low penetration rate. Past studies have shown that switching costs are among the contemporary issues in explaining consumer behaviour. The effect of switching costs, however, has never been test in the area of Takaful. The objective of this study is therefore to empirically test the relationship between switching costs and behavioural intention of the Malay professional conventional policyholders, leading to advancing a Takaful Participation Readiness Model (TPRM). The theory of planned behaviour (TPB) forms the basis in developing the Takaful Participation Readiness Model (TPRM). The investigation begins with a qualitative method. The result of the qualitative study was then used as inputs to the constructs in this study which are knowledge, religiosity, materialism and switching costs. In this study the religious commitment and Takaful knowledge are hypothesised as positively related whereas materialism is hypothesised as negatively related. As this study is a quantitative study, self-administered questionnaires were distributed to the respondents who met the criteria set by the researcher. This study employs exploratory factor analysist (EFA), confirmatory factor analysis (CFA) and structural equation modelling Amos Graphic. The results of this study contribute to Takaful industry by providing an empirical evidence of the relationships between religiosity, knowledge, materialism and switching costs towards Takaful participation readiness is significantly influence by knowledge and switching costs particularly relational costs, uncertainty costs and set-up costs. Although literatures showed that materialism and religiosity do influence behavioural intention, this study however,proved otherwise. For further research, this study should cover not only the professionals in Wilayah Persekutuan and Selangor but to all cities Malaysia including Sabah and Sarawak.